2015
DOI: 10.1097/ta.0000000000000570
|View full text |Cite
|
Sign up to set email alerts
|

Just-in-time learning is effective in helping first responders manage weapons of mass destruction events

Abstract: Therapeutic/care management study, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…7,10 These findings would support the development and implementation of "just-in-time" training programs by organizations that might plan to utilize medical student volunteers. 11,12 These programs may enhance student confidence, willingness to volunteer, and address the concerns of medical students that they lack the required skills to be of use.…”
Section: Discussionmentioning
confidence: 99%
“…7,10 These findings would support the development and implementation of "just-in-time" training programs by organizations that might plan to utilize medical student volunteers. 11,12 These programs may enhance student confidence, willingness to volunteer, and address the concerns of medical students that they lack the required skills to be of use.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in both simulated and actual emergency or pandemic scenarios have demonstrated the efficacy of JIT training to enhance responder preparedness. [34][35][36] Furthermore, among survey respondents, employee health monitoring postencounter with a potentially infectious patient was lacking. It would benefit EMS agencies to conduct regular employee health monitoring in scenarios with potential exposure to HIDs to protect both the responders and communities in which they serve.…”
Section: Discussionmentioning
confidence: 99%
“…3 Several simultaneous strategies were suggested to accomplish the aforesaid, including regularly posted information on EMS national organization Web sites, organizational changes that promote increased communication about HIDs and safety culture, expanding upon existing training guidelines, and using existing national training resources. 34,39 For US EMS, improving practitioner education and training may result in enhanced preparation, capability, willingness, and comfort to respond to potential HID scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…To increase staff capacity for surge Level-3 ICU care, sixty teams of non-ICU trained physicians, nurses, and bio-technicians underwent rapid simulation-based training for critically ill patient care at the Israel Center for Medical Simulation (MSR) [4]. The surgical trauma team and MSR experts developed and implemented this training program.…”
Section: Just-in-time Trainingmentioning
confidence: 99%